2014
DOI: 10.1007/s10008-014-2637-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of amorphous cobalt-boron alloy/highly ordered mesoporous carbon nanofiber arrays as advanced pseudocapacitor material

Abstract: Mesoporous carbon electrodes have been doped with Co-B nanoparticles via a chemical reduction approach and successfully used for pseudocapacitor application. The morphology is investigated by powder X-ray diffractions (PXRDs), small-angle X-ray scattering (SAXS), inductively coupled plasma (ICP), and transmission electron microscope (TEM). The TEM image displays that the Co-B is highly dispersed along the mesoporous carbon support which are critical for the pseudocapacitor application. Cobalt-boron/ highly ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Although the hard-template method has its inherent drawbacks in the sacricial use of hard templates, insufficient stabilities of replicated mesostructures and a complex operational process, it has a wider use in the preparation of MC because it simply allows a carbon source to sediment onto the surface without the need for additional forces at the laboratory level. At the same time, some "hard templates" with similar functions have played important roles in the formation of mesopores and carbon monoliths, such as rigid silicates in composites, which can greatly reduce structural shrinkage during carbonization, creating large mesopores; 39 other novel templates including halloysite, 499 polyurethane foam, 52 cordierite 116,164 and crab shell 195,197,198 also improve this method on different scales. In any case, the method of using natural complex templates to synthesize MC materials has received extensive attention among materials chemists and should be promoted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the hard-template method has its inherent drawbacks in the sacricial use of hard templates, insufficient stabilities of replicated mesostructures and a complex operational process, it has a wider use in the preparation of MC because it simply allows a carbon source to sediment onto the surface without the need for additional forces at the laboratory level. At the same time, some "hard templates" with similar functions have played important roles in the formation of mesopores and carbon monoliths, such as rigid silicates in composites, which can greatly reduce structural shrinkage during carbonization, creating large mesopores; 39 other novel templates including halloysite, 499 polyurethane foam, 52 cordierite 116,164 and crab shell 195,197,198 also improve this method on different scales. In any case, the method of using natural complex templates to synthesize MC materials has received extensive attention among materials chemists and should be promoted.…”
Section: Discussionmentioning
confidence: 99%
“…196 Aer that, this crab shell templating method has also been pursued and developed by other researchers. 197,198 To develop a facile template-free method for the preparation of MC nanobers, Li et al reported a novel self-templating method for the preparation of MC nanobers with a 3D interconnected mesoporous structure and large surface area using ethylene glycol as the carbon precursor and Zn(CH 3 COO) 2 as a structure-building agent and porogen. 199 Electrospinning is a mature technology used in the production of ber materials, which has been successfully employed to fabricate MC nanobers.…”
Section: The Synthesis Of Special Morphologiesmentioning
confidence: 99%